Proliferation and osteogenic activity of fibroblasts induced with fibronectin - Zhang,W.-H. (2017)
The aim of this study was to determine the proliferation and osteogenic activity of fibroblasts induced with fibronectin and their possible dose-dependent relationship. The fibroblasts obtained by tissue explants adherent method were induced with fibronectin at different concentrations of 0, 10, 20, 40, 60, and 80 μg/mL for 14 days. The 3H-thymidine and 3H-proline incorporation test was used to evaluate the synthesis of DNA and collagen by fibroblasts, respectively. The mineralized nodules and osteocalcin secretion, as vital osteogenic indicators, were detected with tetracycline labeling and 125I-labeled competitive immunoassay, respectively. Fibronectin significantly increased the synthesis of DNA and collagen by fibroblasts, especially at the concentration of 40 μg/mL (P<0.05). The increased secretion of osteocalcin in the supernatant was also statistically significant at the concentration of 40 μg/mL (P<0.05). The mineralized nodules with trabecula-like structure derived from induced fibroblasts were positive for tetracycline labeling. The granulation tissue-derived fibroblasts induced with fibronectin exhibited increased proliferative, functional and osteogenic potential. Fibroblasts are considered a possible in situ stem cell in tissue engineering.